1991
DOI: 10.1093/oxfordjournals.eurheartj.a059919
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery spasm induced by 5-fluorouracil

Abstract: We report a case of coronary artery spasm induced by 5-fluorouracil. The symptoms occurred during continuous intravenous infusion of the drug, and a coronary spasm was visualized at angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Coronary vasospasm has historically been accepted as the main contributor to this clinical entity. Ultrasound and angiographic studies demonstrate both coronary artery and brachial artery vasospasm following 5-FU infusion [6,7,8]. 5-FU has also been shown to induce the vasoconstriction of vascular smooth muscle cells in vitro via the activation of protein kinase C, which resolves with administration of protein kinase inhibitors [9].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary vasospasm has historically been accepted as the main contributor to this clinical entity. Ultrasound and angiographic studies demonstrate both coronary artery and brachial artery vasospasm following 5-FU infusion [6,7,8]. 5-FU has also been shown to induce the vasoconstriction of vascular smooth muscle cells in vitro via the activation of protein kinase C, which resolves with administration of protein kinase inhibitors [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound and angiographic studies demonstrate both coronary artery and brachial artery vasospasm following 5-FU infusion [21][22][23]. Prior case reports reveal disease-free coronary arteries on angiography [24].…”
Section: Coronary Vasospasmmentioning
confidence: 95%
“…Although the mechanism of cardiotoxic eff ects of 5-FU is not clear, coronary artery spasm, autoimmunemediated injury of the myocardium, endothelial damage, thrombogenic eff ects or thrombus formation, direct myocardial toxicity causing necrosis and accumulation of metabolites have been suggested to play a role 4 . Th e most frequently suggested mechanism is the coronary vasospasm caused by 5-FU itself or its metabolites (fl uoro beta alanine and fl uoro acetate).…”
Section: Discussionmentioning
confidence: 99%
“…Th e therapy was discontinued and the patient was transferred to our intensive care unit because the electrocardiogram (ECG) showed ischemic changes. Th e fi rst ECG showed ST elevation and peaked T waves in D I-III , aVL, aVF and V [2][3][4][5][6] derivations as well as reciprocal changes in aVR and V I ( Figure 1). Detailed history revealed that a coronary angiography revealing non-pathological fi ndings was performed two weeks ago as a result of a similar clinical picture in another center.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation